2017
DOI: 10.1159/000485820
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 and Ghrelin Attenuate High Glucose/High Lipid-Induced Apoptosis and Senescence of Human Microvascular Endothelial Cells

Abstract: Background/Aims: GLP-1 and ghrelin are common appetite-regulating hormones. Both have multiple functions beyond metabolic regulation. However, the effects of GLP-1 and ghrelin on endothelial biology are not fully understood. Here, we investigate the roles of GLP-1 and ghrelin in microvascular endothelial apoptosis and senescence. Methods: Human microvascular endothelial cells (HMECs) were exposed to high glucose/high lipid (HG/HL) conditions and treated with GLP-1 or ghrelin. Cellular apoptosis, senescence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Ghrelin is also implicated in protecting vascular endothelial cells and preventing various stimulus-induced apoptosis. Liao et al reported that ghrelin attenuated high glucose and lipid-induced apoptosis and senescence of human microvascular endothelial cells [16]. Besides, ghrelin may act as a survival factor in cardiomyocytes H9c2 through inhibiting apoptosis and oxidative stress [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is also implicated in protecting vascular endothelial cells and preventing various stimulus-induced apoptosis. Liao et al reported that ghrelin attenuated high glucose and lipid-induced apoptosis and senescence of human microvascular endothelial cells [16]. Besides, ghrelin may act as a survival factor in cardiomyocytes H9c2 through inhibiting apoptosis and oxidative stress [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Senescence of the endothelial cells is not only due to shortening of their telomeres but may also be induced by such factors as high glucose, Angiotensin II or oxidative stress [6, 7, 8]. These factors play an important role in various types of pathologies of the cardiovascular system in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of cholesterol enriches the connotation of lipotoxicity, which contributes to the development of T2DM [37,38]. GLP-1 as a promising anti-diabetic drug, could improve lipid accumulation and inflammation in hepatocytes [19,20,39]. However, the mechanism of this effect is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the key role played by GLP-1 in mediating lipid metabolism, much researches has aimed to understand the cellular and molecular mechanisms involved [18,19,40]. Fat accumulation in the liver is regarded as a key pathogenic factor of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation